Employment-contingent health insurance, illness, and labor supply of women: evidence from married women with breast cancer - Cathy J. Bradley; David Neumark; Zhehui Luo; Heather L. Bednarek (Institute for the Study of Labor (IZA), 2005)
We examine the effects of employment-contingent health insurance on married women's labor supply following a health shock. First, we develop a theoretical model that examines the effects of employment-contingent health insurance on the labor supply response to a health shock, to clarify under what conditions employment-contingent health insurance is likely to dampen the labor supply response. Second, we empirically evaluate this relationship using primary data. The results from our analysis find that - as the model suggests is likely - health shocks decrease labor supply to a greater extent among women insured by their spouse's policy than among women with health insurance through their own employer. Employment-contingent health insurance appears to create incentives to remain working and to work at a greater intensity when faced with a serious illness.
Keywords: 330; health insurance; health shock; cancer; labor supply; Krankenversicherung; Betriebliche Sozialleistungen; Frauenerwerbstätigkeit; Arbeitsangebot; Krankheit; Schätzung; USA